The Influence of Work Culture, Discipline, Employee Behavior, Welfare, Job Satisfaction, and Job Design on Employee Performance - Rakhmad Kavin; Bhika Annisa; Fajar Hermala Kusuma Wardani (Institut Pemerintahan Dalam Negeri, 2025)
This study analyzes the influence of work culture, discipline, employee behavior, welfare, job satisfaction, and job design on employee performance at the Department of Education and Culture of Lahat Regency. Using a quantitative associative method, 92 respondents were selected through proportionate stratified random sampling.Multiple linear regression analysis showed that all variables significantly affected employee performance, with job satisfaction, discipline, and work culture being the most dominant factors. The results highlight the importance of strengthening positive work culture, improving employee welfare, and aligning job design with employee competencies to enhance sustainable performance.